Hopkins, the Self, and God. - Ong, Walter, J. (Heritage., 2015)
In these studies Professor Ong explores some previously unexamined reasons for Hopkins' uniqueness, including unsuspected connections between nineteenth-century sensibility and certain substructures of Christian belief.